The Medo-Persian Names of Herodotus in the Light of the New Evidence from Persepolis - Schmitt, R.
ersch. 1979; = in: J. Harmatta (Ed.), Studies in the Sources on the History of Pre-Islamic Central Asia (Budapest 1979, Akadémiae Kiadó) 29-39.